Role of high shear mixing in improving stability and bio-efficacy of botanical oil in water formulation for early stage mosquito eradication. Issue 2 (February 2020) - Iqbal, Nusrat; Kumar, Natish; Saini, Mahesh Kumar; Dubey, Saurabh; Agrawal, Amrish; Kumar, Jitendra
Abstract: Neem based formulations conventionally being used as dustable powders, wettable powders, emulsifiable concentrates etc for controlling insects and mosquitoes. These formulations are prepared by mechanical mixing or low shear mixing processes. Among these formulations solvent based EC formulation is more common in use, though it have many drawbacks like phyto-toxicity, flammability, environmental contamination and dermal toxicity. Along with these drawbacks stability of the active ingredient is the most concerned problem, as the active ingredients are unstable in solvent based formulations. Neem oil based oil in water emulsion formulation (EW) formulation may be a safer alternative to EC formulation. In the present study, composition and process technology involved in Neem EW formulations were optimized. Different types of the EW formulation has already been formulated, but no investigations were made to prove the influence of high shear mixing, turbulence flow, time duration on the stability of formulation and its bio-efficacy. The main objective of the study is to determine the effect of turbulence stirring duration on droplet size and emulsion stability. The 60 min turbulence flow mixing at 3600 rpm decreased the particle size from 6.7 to 1.2μm. The prepared formulation stability was further confirmed by different analytical techniques like HPLC and FTIR. The 60 min high shear turbulence stirring enhanced the bio-efficacy in terms of 99 % mortality after 24 h at concentration of 500 ppm of 10 EW. Abstract : Bioengineering; Emulsifiable concentrates; flammability; toxicity; high shear mixing; droplet size